Would a Commodity‐based Trade Approach Improve Market Access for Africa? A Case Study of the Potential of Beef Exports from Communal Areas of Namibia. (March 2015) - Naziri, Diego; Rich, Karl M.; Bennett, Ben
<x xml:space="preserve">Abstract</x> Market access for African livestock products has long been stymied by a variety of animal diseases endemic in the region. The concept of commodity‐based trade (CBT) has been advanced to make trade dependent on process‐related attributes of production that ensure freedom from disease rather than the geographical origin of the animals themselves. This article looks at the potential of CBT in improving market access for beef from communal areas of Namibia, which have historically been excluded from high‐value export markets. Model results suggest only modest gains from CBT, given the substantial costs of compliance with SPS and quality standards required for high‐value markets. Regional markets may still offer the best option for beef exports from these areas.